2010
DOI: 10.1055/s-0029-1243949
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging for characterization of high grade dysplasia and specialized intestinal metaplasia in Barrett’s esophagus: a meta-analysis

Abstract: NBI with magnification is accurate with high diagnostic precision for diagnosis of HGD in Barrett's esophagus on the basis of irregular mucosal pit patterns and/or irregular microvasculature. NBI has high sensitivity but poor specificity for characterizing SIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 22 publications
0
109
0
4
Order By: Relevance
“…12 Narrowband imaging reveals some glandular features that have been documented and have been used to identify neoplasia with high sensitivity 12,13 but low specificity in identifying Barrett's metaplasia. 15 Since VFI uses a nuclear stain, it provides a more direct assessment of glandular architecture. The added benefit of using VFI is the potential for implementing high-resolution imaging at the same time, thus providing the ability to monitor nuclear changes at two different scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Narrowband imaging reveals some glandular features that have been documented and have been used to identify neoplasia with high sensitivity 12,13 but low specificity in identifying Barrett's metaplasia. 15 Since VFI uses a nuclear stain, it provides a more direct assessment of glandular architecture. The added benefit of using VFI is the potential for implementing high-resolution imaging at the same time, thus providing the ability to monitor nuclear changes at two different scales.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Moreover, reported specificities for detecting BE are as low as 65%. 15 Though both technologies enhance mucosal changes in different ways, signal differences have been shown to aid clinical interpretation of mucosal features. 10,11 However, limitations associated with false positives reinforce the need for new imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…NBI ( Figure 1) is generally the most widely available system, and subsequently the one most studied. NBI was shown to have >90% sensitivity and specificity for the detection of high grade dysplasia or EAC in two meta-analyses (28,32).…”
Section: Advanced Imagingmentioning
confidence: 99%
“…Recent studies have shown a sensitivity of 95% and a specificity of 65% for the detection of BE, and a sensitivity and specificity for the detection of HGD of 96% and 94% respectively (36). The combination of this technique with magnifying endoscopes has led to the identification of specific mucosal and microvascular patterns that are useful for the identification of IM, dysplasia and cancer (36,37). The ability of this technique to study mucosal and vascular patterns, its integration with standard endoscopic devices, and the ease of use, are some of the advantages offered for the evaluation of BE.…”
Section: Diagnosis Of Bementioning
confidence: 99%